ANALISIS KINERJA PETUGAS LAYANAN REGISTRASI TERHADAP HASIL LAYANAN REGISTRASI MAHASISWA PADA UPBJJ-UT MANADO - Bambang Bambang (Jurnal Administrasi Publik, 2016)
UPBJJ-Manado Open University is one of the institutions of State for Higher Education which always serve students academically. UPBJJ-academic services at UT Manado will always continue to be improved in a variety of fields one of them is a service to the Field Register, aim to give satisfaction to the customers in this case are students. Both the poor academic services Student Affairs Registration on UPBJJ-UT Manado will certainly have an impact on a matter of right or wrong personal data of students, both registration Courses and Regsitrasi personal data, because if there are errors of the registration data, it can affect the data is the other students, one of them KTPU data. This type of research is descriptive analytic ie where research is after the incident took place. Zethal (1990: 21-22) states that the benchmark for service quality can be measured by the ten dimensions, namely: 1 Tangibles, consisting of physical facilities, equipment, personnel and communications. 2. Reability, consists of the ability of service units in creating service promises. 3. responsivenes, willingness to help the consumer is responsible for the quality of services provided. 4. Competence, its demands good knowledge and skills by personnel in providing services. 5. Courtesy, attitude or behavior hospitable, friendly, responsive to the desires of consumers, as well as willing to carry out contacts or personal relationships. 6. Credibility, fairness in every effort that attract public confidence. 7 Security, services provided should be guaranteed free from various hazards and risks. 8. Access, there is the ease of establishing contact and approach. 9. Communication, membari willingness to listen to the voice service, the customer desires or aspirations, as well as a willingness to always convey new information to the public. 10. Understanding the Customer, make every effort to understand the needs of customers. The research concludes that the performance of workers on the results of services Registration Student Registration at UPBJJ-UT Manado are at an excellent level. This is evidenced by the results of analysis of responses to the service of registration staff have a very high satisfaction rate that is equal to 95.67%, the students are satisfied with the services provided in the Registration officer UPBJJ-UT Manado.